1993
DOI: 10.1128/aem.59.9.2864-2867.1993
|View full text |Cite
|
Sign up to set email alerts
|

Thermostability of Fumonisin B 1 , a Mycotoxin from Fusarium moniliforme , in Corn

Abstract: Fumonisin B1 (FB1) is a mycotoxin from Fusarium moniliforme that is frequently associated with corn. Thermal treatments are used in many processes concerning this cereal and its derivatives. The thermostablity of this toxin in dry contaminated corn, resulting from F. monUiforme culture, was studied in different time-temperature combinations. FB1 was quantified by instrumentalized thin-layer chromatography after a two-step sequential development and postchromatographic derivatization byp-anisaldehyde. The ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…No loss of FB 1 was observed when F. moniliforme culture material was boiled in water for 30 min (Alberts et al 1990). Dupuy et al (1993), however, reported a 50% reduction in FB 1 levels when dry contaminated corn culture material was heated for 10, 30, and 175 min, and 8 hr at 150, 125, 100, and 75°C, respectively. Scott and Lawrence (1994) reported that FB 1 , when heated at 190°C for 60 min, was ≈20% recovered in dry corn meal and ≈42% recovered in moist corn meal.…”
Section: Resultsmentioning
confidence: 90%
“…No loss of FB 1 was observed when F. moniliforme culture material was boiled in water for 30 min (Alberts et al 1990). Dupuy et al (1993), however, reported a 50% reduction in FB 1 levels when dry contaminated corn culture material was heated for 10, 30, and 175 min, and 8 hr at 150, 125, 100, and 75°C, respectively. Scott and Lawrence (1994) reported that FB 1 , when heated at 190°C for 60 min, was ≈20% recovered in dry corn meal and ≈42% recovered in moist corn meal.…”
Section: Resultsmentioning
confidence: 90%
“…Recent reports indicate the presence of fumonisins in several countries, principally in maize-based products (Pittet et al 1992;Sydenham et al 1992b). Heat treatments that have been studied, or used for decontamination or destruction (Dupuy et al 1993), have not proved fully satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…In the next 3 plots (NG-6, NG-8, NG-15), the values measured after harvest were the highest. Since the decrease in fumonisin at a higher temperature begins at 100-120 o C (Dupuy et al, 1993), the higher values suggest that a number of infection nodes were sampled during sampling. Within an item mycotoxins are typically unevenly distributed, so we have to take a sample from multiple locations for representative results.…”
Section: Resultsmentioning
confidence: 99%